Social Media Trap: Exploring the Prevalence of Social Networking Addiction and its Mental Health Outcomes among University Students of Balochistan - Dr. Saima Ambreen, Rahat Ullah (IJoLIS, 2024)
Purpose: This study explored the social media trap by examining the prevalence of Social Networking Addiction (SNA) among university students of Balochistan, Pakistan. Study further explored association and predictive influence of social networking addiction on mental health outcomes (depression, anxiety, and stress for the current study).